Platelets and neurovascular inflammation - Langer, Harald F.; Chavakis, Triantafyllos (Thrombosis and Haemostasis, 2013)
Platelets participate in haemostasis and in thrombus formation in health and disease. Moreover, they contribute to inflammation and cooperate with immune cells in a magnitude of inflammatory/immune responses. Although the inflammatory response has been recognised to be critical in neuronal diseases such as Alzheimer´s disease or multiple sclerosis and its mouse counterpart, experimental autoimmune encephalomyelitis, the participation of platelets in these diseases is poorly investigated so far. Emerging studies, however, point to an interesting crosstalk between platelets and neuroinflammation. For instance, when the integrity of the blood brain barrier is compromised, platelets may be relevant for endothelial inflammation, as well as recruitment and activation of inflammatory cells, thereby potentially contributing to central nervous tissue pathogenesis. This review summarises recent insights in the role of platelets for neurovascular inflammation and addresses potential underlying mechanisms, by which platelets may affect the pathophysiology of neurovascular diseases.
Keywords: Platelets; neuroinflammation